2019
DOI: 10.1038/s41467-019-12381-5
|View full text |Cite
|
Sign up to set email alerts
|

Fungal dissemination is limited by liver macrophage filtration of the blood

Abstract: Fungal dissemination into the bloodstream is a critical step leading to invasive fungal infections. Here, using intravital imaging, we show that Kupffer cells (KCs) in the liver have a prominent function in the capture of circulating Cryptococcus neoformans and Candida albicans, thereby reducing fungal dissemination to target organs. Complement C3 but not C5, and complement receptor CRIg but not CR3, are involved in capture of C. neoformans. Internalization of C. neoformans by KCs is subsequently mediated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 58 publications
3
74
0
Order By: Relevance
“…Deposition of iC3b facilitates recognition by complement receptor 3 (CR3), that enhances phagocytosis, reactive oxygen species (ROS) production, leukocyte trafficking, and migration of macrophages and neutrophils (Hostetter, 2008;Netea et al, 2008). Macrophages in the kidney and liver are also involved in the clearance of pathogenic fungi (Lionakis et al, 2013;Coelho and Drummond, 2019;Sun et al, 2019). CR3 activation also leads to enhanced NET formation and pro-and anti-inflammatory cytokine production by both neutrophils and macrophages (Löfgren et al, 1999;Huang et al, 2015;Lukácsi et al, 2017).…”
Section: Overview Of the Complement Cascadementioning
confidence: 99%
“…Deposition of iC3b facilitates recognition by complement receptor 3 (CR3), that enhances phagocytosis, reactive oxygen species (ROS) production, leukocyte trafficking, and migration of macrophages and neutrophils (Hostetter, 2008;Netea et al, 2008). Macrophages in the kidney and liver are also involved in the clearance of pathogenic fungi (Lionakis et al, 2013;Coelho and Drummond, 2019;Sun et al, 2019). CR3 activation also leads to enhanced NET formation and pro-and anti-inflammatory cytokine production by both neutrophils and macrophages (Löfgren et al, 1999;Huang et al, 2015;Lukácsi et al, 2017).…”
Section: Overview Of the Complement Cascadementioning
confidence: 99%
“…CRIg expression was largely restricted to tissue macrophages, particular in KCs (25,26). This expression profile correlates with the indispensable role of CRIg in KC-mediated immune clearance of various blood-borne microbial species, including parasites (27), fungi (28), and virus (29), all in a complement-dependent manner.…”
Section: Kupffer Cells Are Immune Sentinels In the Liver Sinusoids Wimentioning
confidence: 55%
“…Moreover, Kupffer cells (macrophages residing in the liver) have been shown to have a protective effect. Using intravital imaging, a recent publication demonstrated that Kupffer cells have a function in clearing C neoformans and inhibiting its growth, thus reducing its spread to other organs 25 . Patients with liver disease, particularly cirrhosis, may have impaired Kupffer cell activity, providing a possible mechanism for the development of cryptococcosis in this specific patient population.…”
Section: Microbiology and Pathogenesismentioning
confidence: 99%